The Influence of Gaul Language on The Use of Indonesian Among Students of Stiepar Yapari, Bandung City - Dimas Afrito; Heri Isnaini (An International Journal Tourism and Community Review, 2024)
In everyday life, humans are never separated from the use of language. With language, humans can communicate with one another, convey ideas, and so on. Slang​ is style language which is development or modification from various type language , incl Indonesian so​ Language slang No own A structure style definite language .​ Most of the words are deep Language slang teenager is translations , abbreviations , etc pun . However , sometimes strange, difficult words were also created tracked origin at first . Slang​ is many languages​ used by groups teenager era Now this , incl student Stiepar Yapari is in the majority understand languages slang so that study about Language slang interesting For discussed . Study​​ This aims to determine usage Language slang among people student Stiepar Yapari , and knowing impact use Language slang among people student Stiepar Yapari . Method used in study This is descriptive qualitative . Data collection techniques include: questionnaire . The research results show that student Stiepar Yapari knowing slang terms , indicated by obtaining a percentage of 100%, However Thus, respondents rarely use slang in their daily lives considering that Stiepar Yapari is a tourism campus so students are not recommended use slang .​ Benefit from study This that is For become material learning for student that We must know impact Good the bad Language slang to life outside as well as in the environment campus .